2014
DOI: 10.3329/jbau.v11i1.18221
|View full text |Cite
|
Sign up to set email alerts
|

Effects of probiotics and enzymes on growth performance and haematobiochemical parameters in broilers

Abstract: An study was conducted on "Cobb-500" broiler chicks to evaluate the effects of probiotics and enzymes supplementation on growth performance, haematological and biochemical parameters. A total of 20, fourteen days old broiler chicks were divided randomly into four groups using five broiler chicks in each group. Group A was designated as control group was given only normal broiler ration and rest of the groups were fed probiotics and enzymes, [Group B (probiotic Microguard® @ 1 gm/L), Group C (enzymes preparatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
20
1
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 9 publications
7
20
1
3
Order By: Relevance
“…It also successfully improves immune status of broiler chicks. Probiotics increases physiological activity and production performance of broiler chicken which support the recorded study (Rahman et al, 2013; Ahmed and Taghi, 2006; Kabir et al, 2004).…”
Section: Resultssupporting
confidence: 76%
See 2 more Smart Citations
“…It also successfully improves immune status of broiler chicks. Probiotics increases physiological activity and production performance of broiler chicken which support the recorded study (Rahman et al, 2013; Ahmed and Taghi, 2006; Kabir et al, 2004).…”
Section: Resultssupporting
confidence: 76%
“…Rahman et al (2013) and Pazhanivel and Balachandran (2014) reported that serum ALT level was significantly reduced in chicken with probiotics and phytoextracts treated group, respectively. The recorded present study also supported by Sarker et al (2014).…”
Section: Effects Of Probiotics and Phytoextracts On Biochemical Parammentioning
confidence: 96%
See 1 more Smart Citation
“…In addition, water supplementation of enzymes may lessen the harmful effects of aggressive heat exposure on enzyme activities when the pelleting temperature exceeds 85 • C and can replace expensive post-pelleting sparing systems [25]. Enzyme supplementation in drinking water significantly increased the body weight of broilers during different periods of growth, from 14 to 35 days of age, from 20 to 41 days, and from 20 to 40 days of age [26][27][28][29]. In addition, broilers that received multienzymes through drinking water recorded the highest weekly weight gain when compared to those given enzymes through the feed, and both groups had higher growth than unsupplemented controls [24].…”
Section: Introductionmentioning
confidence: 99%
“…To ensure maximum production, feeding and management practices are very important. Modern feeding practice involves the use of probiotics, growth promoters, balanced diet, antibiotics, steroids and so many new concepts (Rahman et al, 2013).…”
Section: Introductionmentioning
confidence: 99%